3-(4-Methylbenzylidene) camphor induced reproduction toxicity and antiandrogenicity in Japanese medaka (Oryzias latipes). (June 2020) - Liang, Mengmeng; Yan, Saihong; Chen, Rui; Hong, Xiangsheng; Zha, Jinmiao
Abstract: To assess the toxic effects of 3-(4-Methylbenzylidene) camphor (4-MBC) at environmentally relevant concentrations on the reproduction and development of Japanese medaka ( Oryzias latipes ), adult paired medaka (F0) were exposed to 5, 50, and 500 μg/L 4-MBC for 28 d in the current study. The fecundity and fertility were significantly decreased at 500 μg/L 4-MBC ( p  < 0.05). Histological observations showed that spermatogenesis in F0 males was significantly inhibited at 50 and 500 μg/L 4-MBC, similar to the effects obtained with all treatments of plasma 11-ketotestosterone ( p  < 0.05). Moreover, the plasma vitellogenin and estradiol levels in F0 females were significantly increased at 5 μg/L 4-MBC ( p  < 0.05). All the transcripts of hypothalamic-pituitary-gonadal (HPG) axis-related genes tested in the brains and gonads of males were significantly increased at all treatments, similar to the effects obtained for erα, erβ and vtg in the livers and in contrast to those found for arα in the livers ( p  < 0.05). Equal numbers of embryos were exposed to tap water and 4-MBC solutions. Significantly increased times to hatching, decreased hatching rates and decreased body lengths at 14-day post-hatching (dph) were obtained at 500 μg/L 4-MBC treatment ( p  < 0.05). The cumulative death rates at 14 dph were significantly increased with all the treatments ( p  < 0.05). Therefore, our results showed that long-term exposure to 50 and 500 μg/L 4-MBC causes reproductive and developmental toxicity and thus provide new insight into antiandrogenicity and the mechanism of 4-MBC in Japanese medaka. Graphical abstract: Image 1 Highlights: 4-MBC exhibited reproductive toxicity and antiandrogenicity in Japanese medaka. 4-MBC significantly decreased plasma 11-ketotestosterone levels in males. 4-MBC induced transcriptomic responses in HPG-axis of madaka. 4-MBC significantly inhibited spermatogenesis at 50 and 500 μg/L treatments.